History and Empirical: The Influence of Badan Usaha Milik Desa (BUMDes) as Joint Venture on the Brotherhood Principle on Village Economic Independence - Burhanuddin Burhanuddin*; Agussalim Agussalim; Wahyuni Wahyuni (Universitas Syiah Kuala, 2023)
This study aims to analyze and describe